The facial measurements in health workers at Dr. Sardjito General Hospital, Yogyakarta - Nadiya Husna Aliya; Neni Trilusiana Rahmawati; Janatin Hastuti; Sri Awalia Febriana (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2023)
The appropriate mask is based on facial anthropometric measurements that may be affected by sex, race, age, and body mass index (BMI). This study aimed to determine the difference and relationship between the bizygomatic width (BW) and nasion-menton height (NMH) with sex and BMI in health workers. This descriptive-analytical study used a cross-sectional method. The subjects were 39 health workers (nurses and doctors) at Dr. Sardjito General Hospital, Yogyakarta consisting of 15 male subjects and 24 female subjects, aged between 25-55 years old. Anthropometric measurements were performed on the subjects, including body weight, height, NW, and NMH. The data were analyzed using the Shapiro-Wilk test, independent t-test, and Pearson’s test. There was a significant difference in the BW between male and female subjects (p<0.05), with the males’ BW (13.1 ± 0.76 cm) being larger than that of the female subjects (12.35 ± 0.62 cm). There were no differences in the BMI and nasion-menton height between the male and female subjects (p>0.05). The Pearson’s test results showed no significant relationship between the BW with BMI in both the male subjects (r=0.351; p=0.199) and the female subjects (r=0.349; p=0.094), and between the nasion-menton height with BMI in both the male subjects (r=0.101; p=0.721) and the female subjects (r=0.390, p=0.060). In conclusion, the males’ BW was larger than the female health workers. It is necessary to consider facial anthropometric measurements in face mask manufacturing to provide comfort and good protection.